Mega-tsunami conglomerates and flank collapses of ocean island volcanoes - Paris, Raphaël; Herzog, Manuel; Schukraft, Gerd (Marine geology, 2018)
Marine conglomerates at high elevation on the flanks of ocean islands are usually interpreted as evidence of mega-tsunamis generated by volcano flank collapses, although their origin is sometimes debated (elevated littorals vs. tsunami). In this review, we introduce case studies of well-documented examples of tsunami conglomerates in Hawaii (Pacific Ocean), the Canary and Cape Verde Islands (Atlantic Ocean), and Mauritius Island (Indian Ocean). Other less-documented marine conglomerates are also presented as tsunami candidates. Then, we build a comprehensive picture of the general characteristics of these conglomerates and the different methods that can be applied to date them. Different perspectives of research are proposed, especially on the use of tsunami conglomerates as proxies for better constraining numerical models of ocean island flank collapses and associated tsunamis. We also discuss the possible links between volcano growth, flank instability, and climate.
Available online: 13 October 2017
Gesehen am 21.02.2020